In silico investigation on structure–function relationship of members belonging to the human SLC52 transporter family. Issue 5 (23rd December 2022) - Ben Mariem, Omar; Saporiti, Simona; Guerrini, Uliano; Laurenzi, Tommaso; Palazzolo, Luca; Indiveri, Cesare; Barile, Maria; De Fabiani, Emma; Eberini, Ivano
Abstract: Riboflavin is an essential water‐soluble vitamin that needs to be provided through the diet because of the conversion into flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN), important cofactors in hundreds of flavoenzymes. The adsorption and distribution of riboflavin is mediated by transmembrane transporters of the SLC52 family, namely RFVT1‐3, whose mutations are mainly associated with two diseases, MADD and the Brown‐Vialetto‐Van Laere syndrome. Interest in RFVTs as pharmacological targets has increased in the last few years due to their overexpression in several cancer cells, which can be exploited both by blocking the uptake of riboflavin into the cancerous cells, and by performing cancer targeted delivery of drugs with a high affinity for RFVTs. In this work, we propose three‐dimensional structural models for all three human riboflavin transporters obtained by state‐of‐the‐art artificial intelligence‐based methods, which were then further refined with molecular dynamics simulations. Furthermore, two of the most notable mutations concerning RFVT2 and RFVT3 (W31S and N21S, respectively) were investigated studying the interactions between the wild‐type and mutated transporters with riboflavin.